Genomic characterization of ESBL-producing Salmonella Thompson isolates harboring mcr-9 from dead chick embryos in China - Elbediwi, Mohammed; Tang, Yanting; Yue, Min (Veterinary microbiology, 2023)
The emergence and dissemination of the extended spectrum β-lactamase (ESBL)-producing Enterobacteriaceae harbouring antimicrobial resistance (AMR) genes has diminished the potential options for treating multidrug-resistant (MDR) bacterial infections. Until now, numerous studies reported the spreading of critical plasmid-borne AMR genes from different sources worldwide. While the knowledge on the occurrence of the plasmid-borne AMR genes, especially mcr genes in the dead chick embryos, remains obscure. A retrospective study was conducted to detect the presence of the mcr genes in forty-five Salmonella enterica isolates recovered from 2139 dead chick embryo samples, from breeding chicken hatcheries in Henan, China. Using multiplex PCR, we found only four isolates out of the forty-five were mcr-9-positive. These four isolates were found to be MDR, ESBL- producing and showed resistance to 10 antimicrobial drugs. Additionally, mcr-9 harbouring plasmids were successfully transferred into Escherichia coli (E. coli) J53 by conjugation and the mcr-9 gene was confirmed by PCR. We also found that the transconjugants exhibited higher MICs for ampicillin, gentamycin and colistin than the recipient. Whole-genome sequence analysis showed that the four isolates belonged to Salmonella Thompson ST26 and harboured IncHI2 plasmid replicon. Furthermore, the mcr-9 harbouring plasmids were reconstructed using in silico tools and found to be carried other AMR genes (blaDHA-1 and qnrB4). The studied isolates carried the typical virulence factors from Salmonella pathogenicity islands 1 and 2 (SPI-1 and SPI-2), in addition to pef and csg operons which are important in host adhesion and biofilm formation. The mgtC gene, which is involved in phagocytosis, has also been identified. Together, the increase in the phenotypic resistance of the transconjugants and the plasmid in silico reconstruction analysis confirmed that the corresponding resistance genes might be located together on the same plasmid. To track the potential phylogenomic relations of our detected ESBL S. Thompson isolates, we constructed a phylogenomic tree with available ESBL S. Thompson genomes (n = 26) that were reported worldwide. The studied isolates were independently clustered together with four other Chinese isolates of food origin in one clade, providing strong evidence of a potential recent and wide dissemination of ESBL S. Thompson across the food chain in China. In conclusion, we report the detection of four highly virulent ESBL-producing S. Thompson ST26 isolates harbouring mcr-9 gene obtained from dead chick embryos in Henan, China. •Detection of ESBL-producing Salmonella Thompson isolates harboring mcr-9 from dead chick embryos in China.•Conjugative IncHI2 plasmid play a critical role in AMR genes dissemination.•Co-occurrence of mcr-9, qnrB4 and blaDHA-1 genes on the same plasmid.